Improving Student Creativity and Collaboration in IPAS through Project-Based Learning in Class X SMKS Muhammadiyah Bungoro - Ade Fitriani; Elpisah Elpisah; Syarifuddin Syarifuddin (International Journal of Social Welfare and Family Law, 2025)
This study aims to: (1) describe the level of creativity in Grade X students at SMKS Muhammadiyah Bungoro, (2) examine the implementation of the Project-Based Learning (PBL) model in the classroom, and (3) analyze the improvement in students’ collaborative skills through PBL. The research employs a Classroom Action Research (CAR) method conducted in two cycles, each consisting of planning, action implementation, observation, and reflection. The study involved 25 Grade X students at SMKS Muhammadiyah Bungoro. Data collection techniques included observation, documentation, and interviews, with qualitative data analysis presented in percentage form. The findings indicate that: (1) students' creativity was initially low based on preliminary observations, (2) the implementation of PBL in the IPAS subject significantly enhanced students' creativity, showing improvement in all measured indicators, and (3) the PBL model also improved students' collaborative skills, increasing from 48% in the pre-cycle to 53.85% in Cycle I and 83.65% in Cycle II, surpassing the expected 80% threshold in the "collaborative" category. These findings highlight the effectiveness of PBL in fostering creativity and collaboration among students.